HUBUNGAN KUALITAS TIDUR TERHADAP KADAR GLUKOSA DARAH PASIEN DIABETES MELLITUS TIPE 2 - Lispin Lispin; Tahiruddin Tahiruddin; Narmawan Narmawan (STIKes Karya Kesehatan, 2021)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to abnormal insulin secretion, insulin action, or both. Type 2 DM can not be cured, but can be controlled by controlling blood glucose. People with type 2 diabetes experience clinical and psychological symptoms that cause sleep disorders. The occurrence of sleep disorders will have an impact on increasing the frequency of awakening and difficulty falling asleep again. This sleep dissatisfaction ultimately results in a decrease in sleep quality. The purpose of this study was to determine the relationship of sleep quality on blood glucose levels of type II diabetes mellitus patients in Kendari City Hospital. The design of this study was cross sectional study design. The study was conducted from 15 to 30 October 2019. The population of this study were all patients with type II DM who were treated at the Kendari City Hospital in January-June 2019 with a total of 67 people with a total sample of 41 people taken by simple random sampling technique. The inclusion criteria in this study were patients treated at Kendari City Hospital and patients suffering from Type II DM. The results of this study showed that the majority of respondents had poor sleep quality of 25 people (61.0%), the majority of respondents were normal blood sugar levels of 21 people (51.2%) and there was a relationship between sleep quality and blood glucose levels in Kendari City Hospital with a value of p = 0,011 < 0,05. The conclusion of the study is the relationship between sleep quality and blood glucose levels in the Kendari City Hospital. Suggestions from related parties to increase knowledge and skills about the quality of sleep and care of DM patients so that they can provide professional services to patients, especially DM patients in Kendari City Hospital